Towards Participatory Governance in Overcoming Climate Change: A Study of Stakeholders’ Participation in Forest Governance in Indonesia - Auradian Marta (Universitas Teuku Umar, 2021)
One of the Sustainable Development Goals (SDGs) objectives is to overcome climate change by preventing deforestation and forest degradation. Indonesia is a country with a high rate of deforestation and forest degradation. Therefore, this study aims to analyze stakeholders’ participation in addressing deforestation and forest degradation in transforming forest governance in Indonesia to achieve SDGs. This study applies a qualitative approach, and the data are collected through interviews and examination of documents. The collected data are analyzed by interactive models and theories relevant to the study. The findings of this study indicate that there has been a change in forest governance in Indonesia from top-down into bottom-up forest governance, prioritizing the principles of participatory governance. Indonesia's current forest governance system has involved multi-stakeholders in achieving transparent, accountable, and constitutional forest governance, favouring public interest. Furthermore, local, national, and international Civil Society Organizations (CSOs) also play a role and synergize with the government, private sector, community, and indigenous peoples to encourage improvements in forest governance in Indonesia. Finally, the business community plays a role in sustainable forest management to maintain forest resources and ecosystems. It can be concluded that forest management in Indonesia has led to participatory governance by involving stakeholders, leading to a distribution of roles, authorities, and responsibilities in forest governance in Indonesia.